PROPHETIC EDUCATION: Recognising the Idea of Kuntowijoyo’s Prophetic Social Science - Mohd Masduki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
This study is a further examination on prophetic paradigm developed by Kuntowijoyo, then it is implemented as a basis in Islamic learning. According to Kuntowijoyo, there are three basic pillars in developing this prophetic mission, humanism, liberation, and transcendence. Furthermore, its implications are, first, making prophetic education values as an effort to create Islamic education which is full of love, tolerance, righteousness, respecting the differences and other humanitarian characteristics. Second, Islamic education should follow the mission of Muhammad PBUH as a model in the learning processes. It should refer to Islamic education which teaches wisdom; each human behavior is based on God ‘s rules. Third, science should not be dichotomist. All sciences must have universal values. Therefore, objectification in viewing a science is crucial.